Auditory Steady State Response in the Schizophrenia, First-Degree Relatives, and Schizotypal Personality Disorder - Rass, Olga (2012)
The power and phase synchronization of the auditory steady state response (ASSR) at 40 Hz stimulation are usually reduced in schizophrenia (SZ). The sensitivity of the 40 Hz ASSR to schizophrenia spectrum phenotypes, such as schizotypal personality disorder (SPD), or to familial risk has been less well characterized. We compared the ASSR of patients with SZ, persons with schizotypal personality disorder, first degree relatives of patients with SZ, and healthy control participants. ASSRs were obtained to 20, 30, 40 and 50 Hz click trains, and assessed using measures of power (mean trial power or MTP) and phase consistency (phase locking factor or PLF). The MTP to 40 Hz stimulation was reduced in relatives, and there was a trend for MTP reduction in SZ. The 40 Hz ASSR was not reduced in SPD participants. PLF did not differ among groups. These data suggest the 40 Hz ASSR is sensitive to familial risk factors associated with schizophrenia.